Sub-Acute Toxicity Study of Tiger Milk Mushroom Lignosus tigris Chon S. Tan Cultivar E Sclerotium in Sprague Dawley Rats - Kong, Boon-Hong; Tan, Nget-Hong; Fung, Shin-Yee; Pailoor, Jayalakshmi (Frontiers in Pharmacology, 2016)
Lignosus also known as “Tiger Milk Mushroom”, is classified in the family Polyporaceae and mainly consumed for its medicinal properties in Southeast Asia and China. The sclerotium is known as the part with medicinal value and often used by the natives to treat a variety of ailments. Lignosus tigris Chon S. Tan, one of the species of the Malaysia Tiger Milk mushroom, has recently been successfully cultivated in laboratory. Earlier studies have demonstrated the L. tigris cultivar E sclerotia exhibited beneficial biomedicinal properties. This study evaluated the potential toxicity of L. tigris E sclerotia in a 28-day sub-acute oral administration in Sprague Dawley (SD) rats. L. tigris E sclerotial powder was administered orally at three different doses of 250, 500 and 1000 mg/kg to the SD rats once daily, consecutively for 28 days. Body weight of the rats was recorded and general behavior, adverse effects and mortality were observed daily throughout the experimental period. At the end of the experiment, blood hematology and biochemistry, relative organ weights and histopathological analysis were performed. Results showed that there were no mortality nor signs of toxicity throughout the 28-day sub-acute toxicity study. Oral administration of the L. tigris E sclerotial powder at daily dose up to 1000 mg/kg had no significant effects in body weight, relative organ weight, blood hematological and biochemistry, gross pathology and histopathology of the organs. L. tigris E sclerotial powder did not cause any treatment-related adverse effect in the rats at different treatment dosages up to 1000 mg/kg. As the lethal dose for the rats is above 1000 mg/kg, the no-observed-adverse-effect level (NOAEL) dose is more than 1000 mg/kg.